2005
DOI: 10.1097/01.ccm.0000186368.96146.fb
|View full text |Cite
|
Sign up to set email alerts
|

APOE polymorphism is associated with risk of severe sepsis in surgical patients*

Abstract: In an elective surgical cohort, presence of the APOepsilon3 allele is associated with decreased incidence of severe sepsis and a shorter ICU length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 59 publications
(56 reference statements)
1
29
0
Order By: Relevance
“…ApoE also plays a role in antigen presentation to natural killer T-cells by transporting bacterial lipids to CD1 via dendritic cell LDL receptors (14). Although the impact of apoE on human immunity is poorly understood, the finding that an apoE polymorphism is associated with the risk of severe sepsis in surgical patients (15) supports a role for apoE in human host defense.…”
mentioning
confidence: 92%
“…ApoE also plays a role in antigen presentation to natural killer T-cells by transporting bacterial lipids to CD1 via dendritic cell LDL receptors (14). Although the impact of apoE on human immunity is poorly understood, the finding that an apoE polymorphism is associated with the risk of severe sepsis in surgical patients (15) supports a role for apoE in human host defense.…”
mentioning
confidence: 92%
“…Earlier, it was shown that, among the 22mer helices of apoA-I, only the N-and C-terminal helices were able to associate with phospholipids while the other regions (either effects of the apolipoprotein are independent of its cholesterol-lowering property (99)(100)(101)(102). Polymorphisms in the apoE gene are associated with enhancement of the infl ammatory response and an increase in mortality in animal models and patients with sepsis ( 103,104 ). Deletion of the apoE gene also induces these responses in mice treated with either bacterial lipopolysaccharide (LPS) or infected with bacterial pathogens ( 101,102,105 ).…”
Section: Clinical Evaluation Of the Apoa-i Mimetic Peptide 4fmentioning
confidence: 99%
“…27 In a cohort of 343 patients of mainly Caucasian ethnicity (83.1%), who underwent elective major non-cardiac surgery, Moretti et al found a protective effect of the Apo E3 allele with a lower incidence of severe sepsis after surgery. 20 Those links between ApoE genotypes and inflammation has led to studies that analyzed associations between ApoE genotypes with postoperative CSA-AKI.…”
Section: Apoementioning
confidence: 99%
“…19 ApoE variants influence the outcome of severe sepsis in surgical patients. 20 In the context of cardiac surgery, former studies have linked ApoE genotypes with renal failure, 5,9,21 postoperative changes in neurobehavioral status [22][23][24] and inflammation. 22,[25][26][27][28] As a pro-inflammatory cytokine, TNF plays a key role in the inflammatory response after CPB.…”
Section: Introductionmentioning
confidence: 99%